Study on Microstructure through Scanning Electron Microscope from Welding Repair of Railway Surface 70 ponds / yards with Welding Electrodes E110-16G and E1-UM-350 - Chanpahol, Arawan; Srisawad, Saksirichai (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to find the most effective variable for welding repair of railway’s adhesive surface and apply this welding technology in cooperation with Khon Kaen Permanent way, Maintenance Division of State Railway of Thailand. Microstructure was studied with advanced analysis technology through the Scanning Electron Microscope (SEM) with welding repair of railway surface sizing 70 ponds/yards. Variables of the experiment were 2 types of welding electrodes: E110-16G and E1-UM-350. After welding experiment, the macrostructure was examined and found that the welding zone with E110-16G was deeper and well permeated than welding with E1-UM-350. This was because the Silicon (Si) in welding electrode of the austenite structure affected the ability of welding and permeation. From welding with E110-16G, the structure of ferrite phrase had alternating lengths with pearlite structure in the welding zone. From welding with E1-UM-350, bainite structure was consistently dispersed in the welding zone. However, from microstructure examination in heat-affected zone of the welding with E110-16G, the microstructure was consisted of ferrite phase combined with pearlite structure. Martensite structure was found to occur and consistently disperse without any defect. The martensite structure occurred in the welding with E1-UM-350 and porosity was dispersed in the heat-affected zone.